Janoschs Tausend-Bilder-Lexikon - Janosch (Bassermann, 2002)
Pictorial definitions of one thousand German words.
Lizenz des Mosaik-Verl., München
Keywords: Sachbilderbuch; Children's encyclopedias and dictionaries; German; Wortschatz; Alphabet